High levels of T lymphocyte activation in Leishmania-HIV-1 co-infected individuals despite low HIV viral load - Grinsztejn Beatriz; Mattos Marise S; Oliveira-Neto Manoel P; Goto Hiro; Lindoso Jose; Amato Valdir S; Alexandrino de Oliveira Priscilla; Giacoia-Gripp Carmem BW; Santos-Oliveira Joanna R; Morgado Mariza G; Da-Cruz Alda M (BMC Infectious Diseases, 2010)
Abstract Background Concomitant infections may influence HIV progression by causing chronic activation leading to decline in T-cell function. In the Americas, visceral (AVL) and tegumentary leishmaniasis (ATL) have emerged as important opportunistic infections in HIV-AIDS patients and both of those diseases have been implicated as potentially important co-factors in disease progression. We investigated whether leishmaniasis increases lymphocyte activation in HIV-1 co-infected patients. This might contribute to impaired cellular immune function. Methods To address this issue we analyzed CD4+ T absolute counts and the proportion of CD8+ T cells expressing CD38 in Leishmania/HIV co-infected patients that recovered after anti-leishmanial therapy. Results We found that, despite clinical remission of leishmaniasis, AVL co-infected patients presented a more severe immunossupression as suggested by CD4+ T cell counts under 200 cells/mm3, differing from ATL/HIV-AIDS cases that tends to show higher lymphocytes levels (over 350 cells/mm3). Furthermore, five out of nine, AVL/HIV-AIDS presented low CD4+ T cell counts in spite of low or undetectable viral load. Expression of CD38 on CD8+ T lymphocytes was significantly higher in AVL or ATL/HIV-AIDS cases compared to HIV/AIDS patients without leishmaniasis or healthy subjects. Conclusions Leishmania infection can increase the degree of immune system activation in individuals concomitantly infected with HIV. In addition, AVL/HIV-AIDS patients can present low CD4+ T cell counts and higher proportion of activated T lymphocytes even when HIV viral load is suppressed under HAART. This fact can cause a misinterpretation of these laboratorial markers in co-infected patients.